Minding the Store - Marcus, Stanley (Book collections on Project MUSE., 2001)
Stanley Marcus spent most of his life helping to create the retail enterprise Neiman Marcus, and his business philosophies remain an important part of the training of the store's personnel. This is both a portrait of a man and a celebration of the store that is a well-known landmark in Texas.